Separation of nicotinamide metabolites using a PBr column packed with pentabromobenzyl group modified silica gel - Ozaki, Makoto; Shimotsuma, Motoshi; Hirose, Tsunehisa (Analytical biochemistry, 2022)
Nicotinamide adenine dinucleotide, a coenzyme involved in the activation of sirtuins, contributes to various regulations in vivo. However, highly hydrophilic nicotinamide metabolites are difficult to separate by high-performance liquid chromatography (HPLC) using octadecyl (C18) columns, which operate via hydrophobic interaction. PBr columns packed with silica gel modified with the pentabromobenzyl group having strong dispersion forces show good retention ability for various highly hydrophilic compounds. Additionally, the peak shape obtained with the PBr column did not collapse like that of the HILIC column, even when a large amount of water was injected. Separation of 11 highly hydrophilic nicotinamide metabolites using a PBr column under simple conditions resulted in baseline separation, but separation on a C18 column was not complete. The peak shape for each compound was better than that in previous studies. Furthermore, the separation of nicotinamide metabolites in tomato using a PBr column enable a more sensitive detection than that using a C18 column. Chromatographic Technique [Display omitted] •Nicotinamide metabolites of highly hydrophilic compounds are difficult to separate using a C18 column, which operates on the basis of hydrophobic interaction.•A PBr column packed with a stationary phase similar to 3-(pentabromobenzyloxy)propyl (PBB) could baseline-separate highly hydrophilic nicotinamide metabolites under simple conditions.•The peak shape of the nicotinamide metabolites obtained using the PBr column was better than that of previous studies.